The aesthetic formation of the image of the believer in the poetry of the veterans - ميهوب, علي; عدنان محمّد أحمد (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
Veteran poets in the early days of Islam translated the image of man into poetry, so they painted an aesthetic self-portrait of the pious believer, the mujahid, the Muslim of the divine will, and the glorifier of Islamic values, and an aesthetic image of the martyr believer, showing his physical attributes represented by the brave and daring who rejects grievance and rejects injustice, white temptation, and his moral qualities Represented by Al-Majid Al-Sharif, Al-Saber, Al-Sadiq, Al-Wafi, and the one with good opinion, so that these qualities in their totality form beautiful qualities that combine the beauty of appearance and the glory of the traits So the image of the believer in the poetry of the veterans came on an aesthetic carrier that derives its pillars from the various rhetorical methods, graphic images, and their good use of words and meanings that combine with each other to make this image a model for the true believer, so it was able to read the true dimensions of the meanings of faith, and it was evidence of the desire of the veterans to Changing their pre-Islamic image into a new image that celebrates faith.